Association Between Serum Folate Level and Toxicity of Capecitabine During Treatment for Colorectal Cancer. (25th May 2018) - Chan, Stephen L.; Chan, Anthony W.H.; Mo, Frankie; Ma, Brigette B.Y.; Wong, Kenneth C.W.; Lam, Daisy; Mok, Florence S.T.; Chan, Anthony T.C.; Mok, Tony; Chan, K.C. Allen
Abstract: Background: Folate level was proposed to be a predictor for fluoropyrimidine‐related toxicity. We conducted a prospective study to determine the association between serum and red‐cell folate and capecitabine‐related toxicity in patients with colorectal cancers. Materials and Methods: Eligibility criteria included diagnosis of colorectal cancers; eligible patients who were scheduled to undergo capecitabine monotherapy or capecitabine‐oxaliplatin (CAPOX) for adjuvant or palliative purposes. Exclusion criteria included concomitant radiotherapy or chemotherapy other than capecitabine or CAPOX and creatinine clearance <30 mL/min. Fasting serum and red‐cell folate were measured prior to chemotherapy. Capecitabine was administered at 2, 500 mg/m 2 per day (monotherapy) or 2, 000 mg/m 2 per day (CAPOX) for 14 days every 3 weeks. The toxicity of the first four cycles was documented by clinical investigators who were blinded to folate levels. Results: A total of 144 patients were recruited, of whom 126 were eligible; 40 patients had capecitabine alone, and 86 patients received CAPOX. The rates of grade 2 and grade 3 toxicity were 63.5% and 14.3%, respectively. Nausea and vomiting were the most common grade ≥2 adverse event (47.7%), followed by hand‐foot syndrome (25.4%), diarrhea (23.1%), and neutropenia (22.3%). Combination with oxaliplatin (odds ratio [OR], 2.77; p  = .043) and serum folate (OR, 10.33; p  = .002) were independent predictors of grade ≥2 toxicity. Red‐cell folate was not predictive of toxicity. For every 10 nmol/L increment in serum folate, the risk of grade ≥2 toxicity increased by 9%. Conclusion: Serum folate level, but not red‐cell folate, was associated with higher rate of grade ≥2 toxicity during capecitabine‐based treatment. Excessive folate intake may be avoided before and during capecitabine‐based chemotherapy. Implications for Practice: This is the first prospective study to evaluate the association between serum folate level and capecitabine‐related toxicity in patients with colon cancers. It shows that higher serum folate level is associated with increased risks of moderate to severe toxicity during capecitabine‐based treatment. Excessive folate intake should be avoided before and during capecitabine‐based chemotherapy. Abstract : This article evaluates the association between capecitabine‐related toxicity and serum/red cell folate level in a group of patients who underwent capecitabine‐based chemotherapy for the treatment of colorectal cancer. The rate and type of capecitabine‐related toxicity was examined, with a goal of identifying other clinical predictive parameters for capecitabine‐related toxicity.